Pros, cons and future perspectives – three questions on three dimensional guidance for cardiac catheterization in congenital heart disease - Góreczny, Sebastian; Krings, Gregor; Hijazi, Ziyad; Fagan, Thomas; Berman, Darren; Kenny, Damien; Morgan, Gareth (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2019)
Step changes in angiographic imaging are not commonplace. Since the move from analogue to digital and flat detector plates, two-dimensional imaging technology has certainly evolved but not jumped forward. Of all the routine imaging techniques used in cardiology, angiography has been the last modality to embrace the third dimension. Although the development of rotational angiography was initially for the benefit of neuroimaging and fusion of cross sectional datasets was aimed at the treatment of descending aortic pathology, interventional physicians in congenital and structural cardiology have immersed themselves in this technology over the last 10 years. Like many disruptive technologies, its introduction has divided opinion. We aimed to explore the mindset of those in the field of interventional cardiology who are driving imaging forward. These structured interviews recorded during the 21st Pediatric and Adult Interventional Cardiac Symposium illustrate the challenges and sticking points as well as giving an insight into the direction of travel for three-dimensional imaging and fusion techniques. Covering a wide range of career development, seniority and experience, the interviewees in this article are probably responsible for the majority of the published literature on invasive three-dimensional imaging in congenital heart disease.